2020
DOI: 10.1021/acschemneuro.0c00096
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Pathological Roles of Cdk5: Potential Directions for Therapeutic Targeting in Neurodegenerative Disease

Abstract: Cyclin-dependent kinase 5 (Cdk5) is a prolinedirected serine (ser)/threonine (Thr) kinase that has been demonstrated to be one of the most functionally diverse kinases within neurons. Cdk5 is regulated via binding with its neuronspecific regulatory subunits, p35 or p39. Cdk5−p35 activity is critical for a variety of developmental and cellular processes in the brain, including neuron migration, memory formation, microtubule regulation, and cell cycle suppression. Aberrant activation of Cdk5 via the truncated p3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 148 publications
2
61
0
1
Order By: Relevance
“…P35, an activator of Cdk5, hydrolyses into p25 and subsequently binds to Cdk5 when Calpain is activated, causing abnormal activation of Cdk5. The Cdk5/p25 complex induces neurotoxicity, cell death and various diseases [39][40][41]. The results of the present study demonstrate the role of the above pathway in the regulation of p-SYN1 (ser-553); that is, microwave exposure induces higher levels of Calpain, which subsequently promotes Cdk5/p25 complex formation, potentially leading to the reduction of p-SYN1 (ser-553) as depicted in in Figure 9.…”
Section: Discussionsupporting
confidence: 54%
“…P35, an activator of Cdk5, hydrolyses into p25 and subsequently binds to Cdk5 when Calpain is activated, causing abnormal activation of Cdk5. The Cdk5/p25 complex induces neurotoxicity, cell death and various diseases [39][40][41]. The results of the present study demonstrate the role of the above pathway in the regulation of p-SYN1 (ser-553); that is, microwave exposure induces higher levels of Calpain, which subsequently promotes Cdk5/p25 complex formation, potentially leading to the reduction of p-SYN1 (ser-553) as depicted in in Figure 9.…”
Section: Discussionsupporting
confidence: 54%
“…Various studies have reported the overexpression of cell cycle protein regulators, such as CDKs, in the vicinity of NFTs and senile plaques in the post-mortem brains of AD patients [68,90], indicating that the overexpression of the regulators of the cell cycle may be a characteristic feature of AD. Consistently, the administration of CDKIs (inhibitors of CDK1, 2, 4, 5, 7, 9) ameliorated AD symptoms in animal models [91][92][93][94][95][96], corroborating that the cell cycle and mitosis play an important role in AD development and could become important targets of drug research. In this sense, CDKIs have been suggested to be of potential relevance in the treatment of AD [93].…”
Section: Cell Cycle and Admentioning
confidence: 64%
“…Cdk5 activity is crucial after toxic stimuli to avoid initiation of apoptosis, cytoskeletal remodeling, detachment from the glomerular basement membrane, and, eventually, loss of podocytes in the urine. Several studies on Cdk5 in neurological and oncological disorders showed good transferability of results gained in mice to human disease [ 53 , 54 ]. Consequently, it is tempting to speculate that activation of Cdk5 could be a novel therapeutic approach in human inflammatory glomerular disease.…”
Section: Discussionmentioning
confidence: 99%